Penyuluhan Gizi Seimbang untuk Pencegahan Stunting - Wulan Murti; Yulia Nur Khayati (Universitas Ngudi Waluyo, 2024)
Stunting is a chronic malnutrition problem caused by chronic nutritional intake caused by insufficient nutritional intake for a long time due to the provision of food that does not meet nutritional needs. Stunting can occur as a result of malnutrition, especially during the first 1000 days of pregnancy, 270 days during pregnancy plus the first year of 365 days and the second year of 365 days. Those thousand days are a golden opportunity to form healthy and smart children. One way to prevent stunting is to fulfill nutrition and services for pregnant women. Malnutrition at an early age increases infant and child mortality rates, causing sufferers to get sick easily and have less than optimal posture as adults. The cognitive abilities of sufferers are also reduced, resulting in long-term economic losses for Indonesia. The purpose of this activity is to provide education to mothers of toddlers on how to prevent stunting in toddlers. The problem that arises is that the results of the KMS growth chart are below the red line (BGM). Community service will be carried out in 3 stages, namely the First Stage, selecting a group of mothers of toddlers in RT 14 Kampung Pelayaran, Prapatan Village, Balikpapan City. The second stage provides health education on balanced nutrition to prevent stunting. The third stage evaluates the delivery of information about balanced nutrition to prevent stunting. The evaluation results show that there is an increase in the knowledge of mothers of toddlers about balanced nutrition to prevent stunting. It is hoped that the community can improve their ability to understand balanced nutrition for toddlers as an effort to prevent stunting. Abstrak Stunting adalah masalah kurang gizi kronis yang disebabkan oleh asupan gizi kronis yang disebabkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai kebutuhan gizi. Stunting dapat terjadi sebagai akibat kekurangan gizi terutama pada saat 1000 hari pertama kehamilan, 270 hari selama kehamilan ditambah tahun pertama 365 hari dan tahun kedua 365 hari. Seribu hari itu merupakan kesempatan emas untuk membentuk anak yang sehat dan pintar. Salah satu cara mencegah stunting adalah pemenuhan gizi dan pelayanan pada ibu hamil kekurangan gizi pada usia dini meningkatkan angka kematian bayi dan anak, menyebabkan penderitanya mudah sakit dan memiliki postur yang tidak maksimal saat dewasa. Kemampuan kognitif para penderita juga berkurang, sehingga mengakibatkan kerugian ekonomi jangka panjang bagi Indonesia. Tujuan kegiatan ini adalah untuk memberikan edukasi kepada ibu balita bagaimana pencegahan stunting pada balita. Masalah yang muncul adalah hasil KMS grafik pertumbuhan berada dibawha garis merah (BGM). Pengabdian masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama pemilihan kelompok ibu balita di RT 14 Kampung Pelayaran Kelurahan Prapatan Kota Balikpapan. Tahap Kedua memberikan penyuluhan kesehatan mengenai gizi seimbang untuk pencegahan stunting. Tahap Ketiga melakukan evaluasi terhadap penyampaian informasi tentang gizi seimbang untuk pencegahan stunting. Hasil evaluasi didapatkann hasil bahwa terdapat peningkatan pengetahuan ibu balita mengenai gizi seimbang untuk pencegahan stunting. Diharapkan masyarakat dapat meningkatkan kemampuannya dalam pemahaman mengenai gizi seimbang untuk balita sebagai salah satu upaya dalam pencegahan stunting.